Triptan partition in model membranes - Wood, Irene (2014)
In this work, we report a molecular dynamics simulations study of protonated triptans, sumatriptan and naratriptan, in a fully hydrated bilayer of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphatidyl-choline (POPC). The simulations were carried out at two concentrations for each drug. Our results show partition between the lipid head-water interphase and water phase for both triptans, with increasing access to the water phase with increasing concentrations. The triptans were stabilized at the interphase through different specific interactions with the POPC bilayer such as hydrogen bonds, salt bridges, and cation-π. Besides, sumatriptan and naratriptan protonated molecules have no access to the hydrophobic region of the bilayer at the studied conditions. Similar results were found for both drugs, however protonated naratriptan shows slightly higher affinity for the water phase. This behavior was attributed to the bulky lateral amino group in its structure under the studied conditions (drugs were originally placed at the water phase). This work represents a first insight to the comprehensive understanding of triptan partition in model membranes.